Comments on the Appearance of the Journal for the Study of Religion, Nature and Culture - Arnold, Philip P. 1957- (2007)
In Native American religions there has been a shift from expert knowledge to collaborative knowledge—working with indigenous communities on issues of urgent mutual concern. Most urgent are environmental issues. This article explores collaborative relationships with the Onondaga Nation, near Syracuse New York, the Central Fire of the Haudenosaunee (‘People of the Longhouse’ Six Nations Iroquois) Confederacy. The Onondaga Nation is still organized and run according to the ancient ceremonial process—the Great Law of Peace. Because of their strong traditional orientation they have led international efforts for the recognition of indigenous people at the United Nations. Leaders like Oren Lyons and Audrey Shenandoah have brought their message of peace and environmental justice to the world. On 11 March 2005 they filed their ‘Land Rights Action’. Native and non-native have been inspired by this action and several collaborative events have resulted from this bold and principled stand on behalf of the environment.
Keywords: Land Rights; Indigenous Peoples